(untitled) (Journal of the College of Basic Education, 2022)
The study aimed to prepare exercises on the (verti max) device, then to identify the effect of the exercises on developing some biomechanical indicators and the accuracy of the offensive blocking skill in volleyball for young people. As the research sample of (12) players was chosen, the sample was divided into two groups, the first control group and the second experimental group.